Features of Lingual Genres in Contemporary Musical Communication (Linguostylistic Studies, 2015)
The definition of music-lingual genre is offered. The basic conditions of terminological adoption of this concept are outlined, the main approaches to investigation of its functioning are described. Main socio-cultural, stylistic parameters as far as musical levels of expression are characterized. The classification of lingual genres in music has been approached. The main features of lingual genres in music has been described. Theoretical positions of article were illustrated by the examples from the contemporary musical communication in different discourses. The main directions of further studying of lingual genres communication are supposed. Key words: musical-creative genre, musical-lingual genre, genre group, genre types, functions of genre, music communication, music expression. References